The May Bride : A Novel of Tudor England - Dunn, Suzannah (London Abacus, 2015)
From the bestselling author of The Confession of Katherine Howard, the story of two years at the Seymour family home, Wolf Hall, that changed Jane Seymour's life for ever. 'I loved this powerful book and can't recommend highly enough' Martina Cole
Keywords: Jane Seymour, Queen, consort of Henry VIII, King of England, 1509?-1537